Le rôle du Centre excursionniste de Catalogne et de la Société Peñalara dans la patrimonialisation des Pyrénées Aragonaises (fin XIXe – début XXe siècle) - Juan Sevilla (VertigO, 2013)
The first Iberian mountain and excursionists associations are set up during the late 19th century and the beginning of the 20th at the same time that many Alpine clubs in Europe spread. From the very beginning, these associations contact the French mountaineers from the Pyrenees, who are responsible for the scientific, cultural and sportive breakthrough which takes place in the high mountains located in Aragon. As a consequence, clubs such as the Catalonia Excursionist Centre and the Peñalara Society from Madrid start the exploration in the Mid Pyrenees. From then on, these organizations contribute to establish a common “mountain feeling” in the Southern end of the range. The main aim of this article is to emphasize the importance of the Catalonia Excursionist Centre and the Peñalara Society as they play a key role to increase the heritage making process of the area after the first steps made by the French.